A robust multi-objective global supplier selection model under currency fluctuation and price discount - Atousa Zarindast; Seyed Mohamad Seyed Hosseini; Mir Saman Pishvaee (Journal of Industrial Engineering International, 2017)
Robust supplier selection problem, in a scenario- based approach has been proposed, when the demand and exchange rates are subject to uncertainties. First, a deterministic multi-objective mixed integer linear programming is developed; then, the robust counterpart of the proposed mixed integer linear programming is presented using the recent extension in robust optimization theory. We discuss decision variables, respectively, by a two-stage stochastic planning model, a robust stochastic optimization planning model which integrates worst case scenario in modeling approach and finally by equivalent deterministic planning model. The experimental study is carried out to compare the performances of the three models. Robust model resulted in remarkable cost saving and it illustrated that to cope with such uncertainties, we should consider them in advance in our planning. In our case study different supplier were selected due to this uncertainties and since supplier selection is a strategic decision, it is crucial to consider these uncertainties in planning approach.
Keywords: 650; Supplier selection; Robust programming; Discount; Currency exchange rate uncertainty